Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the equation [tex]\(\left(\frac{1}{4}\right)^{x+1}=32\)[/tex], we need to find the value of [tex]\(x\)[/tex].
We can start by expressing both sides of the equation using the same base:
[tex]\[ \left(\frac{1}{4}\right)^{x+1} = 32 \][/tex]
First, note that [tex]\(\frac{1}{4}\)[/tex] can be written as [tex]\(4^{-1}\)[/tex] and [tex]\(32\)[/tex] can be written as [tex]\(2^5\)[/tex]. Hence, we rewrite the equation as:
[tex]\[ (4^{-1})^{x+1} = 2^5 \][/tex]
Next, we need to express [tex]\(4\)[/tex] in terms of base [tex]\(2\)[/tex]. Since [tex]\(4 = 2^2\)[/tex], we have:
[tex]\[ (2^{-2})^{x+1} = 2^5 \][/tex]
Simplify the left-hand side:
[tex]\[ 2^{-2(x+1)} = 2^5 \][/tex]
Now that the bases are the same, we can equate the exponents:
[tex]\[ -2(x+1) = 5 \][/tex]
Distribute the [tex]\(-2\)[/tex] on the left-hand side:
[tex]\[ -2x - 2 = 5 \][/tex]
Solve for [tex]\(x\)[/tex] by isolating it on one side:
[tex]\[ -2x - 2 = 5 \][/tex]
[tex]\[ -2x = 5 + 2 \][/tex]
[tex]\[ -2x = 7 \][/tex]
[tex]\[ x = -\frac{7}{2} \][/tex]
Thus, the correct solution to the equation is:
[tex]\[ \boxed{-\frac{7}{2}} \][/tex]
So the correct answer is option B: [tex]\(-\frac{7}{2}\)[/tex].
We can start by expressing both sides of the equation using the same base:
[tex]\[ \left(\frac{1}{4}\right)^{x+1} = 32 \][/tex]
First, note that [tex]\(\frac{1}{4}\)[/tex] can be written as [tex]\(4^{-1}\)[/tex] and [tex]\(32\)[/tex] can be written as [tex]\(2^5\)[/tex]. Hence, we rewrite the equation as:
[tex]\[ (4^{-1})^{x+1} = 2^5 \][/tex]
Next, we need to express [tex]\(4\)[/tex] in terms of base [tex]\(2\)[/tex]. Since [tex]\(4 = 2^2\)[/tex], we have:
[tex]\[ (2^{-2})^{x+1} = 2^5 \][/tex]
Simplify the left-hand side:
[tex]\[ 2^{-2(x+1)} = 2^5 \][/tex]
Now that the bases are the same, we can equate the exponents:
[tex]\[ -2(x+1) = 5 \][/tex]
Distribute the [tex]\(-2\)[/tex] on the left-hand side:
[tex]\[ -2x - 2 = 5 \][/tex]
Solve for [tex]\(x\)[/tex] by isolating it on one side:
[tex]\[ -2x - 2 = 5 \][/tex]
[tex]\[ -2x = 5 + 2 \][/tex]
[tex]\[ -2x = 7 \][/tex]
[tex]\[ x = -\frac{7}{2} \][/tex]
Thus, the correct solution to the equation is:
[tex]\[ \boxed{-\frac{7}{2}} \][/tex]
So the correct answer is option B: [tex]\(-\frac{7}{2}\)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.